A new troglobiotic species of Hyalella (Crustacea, Amphipoda, Hyalellidae) with a taxonomic key for the Brazilian species - Rodrigues, Stella Gomes; de Pádua Bueno, Alessandra Angélica; Ferreira, Rodrigo Lopes (Zootaxa, 2014)
The freshwater crustaceans from the order Amphipoda occur mainly in cold and temperate climates. However, in the tropics, these animals can be more abundant in subterranean environments, where the temperatures are milder than in surface. Despite being accepted that the number of species of freshwater amphipods in South America is lower when compared to other regions, recent descriptions have shown that its diversity is certainly underestimated. In this study, a new species of the genus Hyalella is described for Brazil, the fourth troglobiotic species of Hyalella for the country and the sixth in the world. The new species was found on the epikarst of a cave in São Paulo state, Southeastern Brazil. Besides, the new species shows typical characteristics from organisms adapted to the subterranean environments, a pattern also observed in the other troglobiotic species of the genus.